Strengthening risk-informed decision-making: scenarios for human vulnerability and exposure to extreme events. Issue 5 (26th August 2020) - Birkmann, Joern; Sauter, Holger; Jamshed, Ali; Sorg, Linda; Fleischhauer, Mark; Sandholz, Simone; Wannewitz, Mia; Greiving, Stefan; Bueter, Bjoern; Schneider, Melanie; Garschagen, Matthias
Abstract : Purpose: Enhancing the resilience of cities and strengthening risk-informed decision-making are defined as key within the Global Agenda 2030. Implementing risk-informed decision-making also requires the consideration of scenarios of exposure and vulnerability. Therefore, the paper presents selected scenario approaches and illustrates how such vulnerability scenarios can look like for specific indicators and how they can inform decision-making, particularly in the context of urban planning. Design/methodology/approach: The research study uses the example of heat stress in Ludwigsburg, Germany, and adopts participatory and quantitative forecasting methods to develop scenarios for human vulnerability and exposure to heat stress. Findings: The paper indicates that considering changes in future vulnerability of people is important to provide an appropriate information base for enhancing urban resilience through risk-informed urban planning. This can help cities to define priority areas for future urban development and to consider the socio-economic and demographic composition in their strategies. Originality/value: The value of the research study lies in implementing new qualitative and quantitative scenario approaches for human exposure and vulnerability to strengthen risk-informed decision-making.